Euphausiid population structure and grazing in the Indian sector of the Antarctic Polar Frontal Zone, during austral autumn - Bernard, Anthony Thomas Firth (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2005)
The trophodynamics of the numerically dominant euphausiid species within a region of high mesoscale oceanographic variability in the southwest Indian sector of the Antarctic Polar Frontal Zone (PFZ) were investigated during the austral autumns April/May) of 2004 and 2005. During the 2004 survey, sub-surface (200 m) temperature profiles indicated that an intense frontal feature, formed by the convergence of the Sub-Antarctic Front (SAF) and the Antarctic Polar Front (APF) bisected the survey area into two distinct zones, the Sub- Antarctic Zone (SAZ) and the Antarctic Zone (AAZ). Total integrated chlorophyll-a (chl-a) biomass was typical for the region (< 25 mg chl-a mâ »Â²), and was dominated by picophytoplankton. Total euphausiid abundance and biomass ranged from 0.1 to 3.1 ind mâ »Â³ and 0.1 to 8.1 mg dwt mâ »Â³, respectively, and did not differ significantly between the stations occupied in the SAZ and AAZ (p > 0.05). The multivariate analysis identified two interacting mechanisms controlling the distribution patterns, abundance and biomass of the various euphausiid species, namely (1) diel changes in abundance and biomass, (2) and restricted distribution patterns associated with the different water masses. Ingestion rates were determined for five euphausiid species. E. triacantha was found to have the highest daily ingestion rate ranging from 1 226.1 to 6 029.1 ng pigm indâ »Â¹dâ »Â¹, while the lowest daily ingestion rates were observed in the juvenile Thysanoessa species (6.4 to 943.0 ng pigm indâ »Â¹ dâ »Â¹). The total grazing impact of the selected euphausiids ranged from < 0.1 to 20.1 Î¼g pigm mâ »Â²dâ »Â¹, corresponding to < 0.15 % of the areal chl-a biomass. The daily ration estimates of autotrophic carbon for the euphausiids suggested that phytoplankton represented a minor component in their diets, with only the sub-adult E. vallentini consuming sufficient phytoplankton to meet their daily carbon requirements. A cyclonic cold-core eddy spawned from the region of the APF located in the southwest Indian sector of the PFZ was the dominant feature during the 2005 survey. The total areal chl-a biomass throughout the region was low, ranging between 5.6 and 11.4 mg chl-a mâ »Â², and was significantly higher within the core of the eddy compared to the surrounding waters (p < 0.05). RMT-8 and WP-2 total euphausiid abundance and biomass estimates were high, and ranged from 0.004 to 0.36 ind mâ »Â³ and 0.065 to 1.21 mg dwt mâ »Â³, and from 0.01 to 18.2 ind mâ »Â³ and 0.01 to 15.7 mg dwt mâ »Â³, respectively. A distinct spatial pattern in the euphausiid community was evident with the Antarctic species, Euphausia frigida, E. triacantha and E. superba predominating within the core of the eddy, while the PFZ waters were characterized by the sub-Antarctic species, E. longirostris, Stylocheiron maximum, Nematoscelis megalops and Thysanoessa gregaria. The eddy edge acted as a transition zone where species from both regions co-occurred. Within the survey area the combined ingestion rate of the six numerically dominant euphausiid species ranged between 0.02 and 5.31 Î¼g pigm mâ »Â²dÂ¹, which corresponded to a loss of between < 0.001 and 0.11 % of the available chl-a biomass. E. triacantha and juvenile T. macura were identified as the dominant grazers. There was no apparent spatial pattern in the grazing activity of the euphausiids within the region of investigation. The average daily rations of the euphausiids examined were < 2 % of their body carbon. The low daily ration of the euphausiids could be ascribed to the predominance of small picophytoplankton in the region of investigation, which are too small to be grazed efficiently by larger zooplankton. The marked spatial patterns in species composition and the elevated abundance and biomass of euphausiids, suggest that the mesoscale eddies contribute to the spatial and temporal heterogeneity of the planktonic community of the PFZ and may represent important foraging regions for many of the apex predators within the region.
Keywords: Euphausiacea -- Antarctic Ocean; Euphausiacea -- Feeding and feeds